A házasságon kívül született gyermek jogállása különös tekintettel a tartásdíj kiszabásának bírói gyakorlatára 1945 és 1950 között Magyarországon - Krausz, Bernadett (Díké - A Márkus Dezső Összehasonlító Jogtörténeti Kutatócsoport folyóirata, 2021)
There was a legal differentiation between children born in and out of wedlock in 1945. The Hungarian State recognised that this differentiation was outdated, thus the Act XXIX of 1946 on the legal status of children born out of wedlock came into force on June 7, 1947. The aims of the Act were that it should cease the differentiation between children born in and out of wedlock and their legal status shall be equal to legitimate children, and the children born out of wedlock (illegitimate children) shall be related to their fathers and their fathers’ kin. It was the first comprehensive regulation regarding child support that came into effect. The study presents the regulations of child support between 1945 and 1950 in Hungary and discloses the court practice regarding child support of the District Court of Zalaegerszeg in the designated period.